FOOD AND FEEDING HABITS OF TWO FRESHWATER FISHES, OMPOK BIMACULATUS AND O. MALABARICUS OF RIVER AMARAVATHY, TAMIL NADU - T. ARTHI; S. NAGARAJAN; A. A. SIVAKUMAR (The Bioscan, 2011)
The two freshwater fishes, Ompok bimaculatus and O. malabaricus are found to be omnivorous, feeding mainly on vegetable matter and fish, which dominated the list with a percentage of 30.04. Vegetable matters take the precedence with an average percentage of 28.65 for twelve months Crustacean adults, crustacean larvae, insect and molluscs are identified as secondary and supplementary foods. The percentage frequency of occurrence of fish and vegetable matter, and crustaceans in the gut contents of both the species are more than the other food items. Feeding intensity was more in December (48.3%) with minimum (34.4%) in May for O. bimaculatus and was more in March (63.5%) with minimum (32%) in October for O. malabaricus The occurrence of empty stomach was found to be more during the peak breeding season, in both the species.